Plant communities of high mountain coniferous forest in the Tancítaro massif, Michoacán, Mexico - Medina García, Consuelo; Gimenez de Azcarate, Joaquin; Velázquez Montes, Alejandro (Instituto de Ecología, A.C., 2020)
Background and Aims: The timberline occurs as an ecosystem harboring unique forest and grassland types comprising outstanding endemic species. These vegetation types, furthermore, are the centers of capturing, recharging and transporting water so that these are regarded as provider´s nodes of environmental services. This is even more significant in intertropical mountains since these harbor large genetic reservoirs. This is the case of the Pico del Tancítaro and surrounding volcanoes, a region between 2600 and 3800 m elevation, in Michoacán, Mexico. The present study aimed to define and characterize the floristic and phytocenotic diversity, as well as recognize distribution patterns of the plant associations along the elevational gradient. Methods: Thirty five inventories were carried out following the phytosociological approach. At each inventory, a list of species, their coverage, and physical and geographical attributes of the site were compiled. Field information was later verified in the laboratory to ensure species identification; “Flora del Bajío y regiones adyacentes” was preferably consulted. Data were further analyzed via multivariate techniques in order to define plant associations. Key results: The 35 inventories were considered as a basis to assemble the vegetation tables that support three plant associations: Gaultherio myrsinoidis-Pinetum hartwegii, Polysticho speciosissimae-Abietetum religiosae and Sibthorpio repentis-Abietetum religiosae; as well as other units of lower rank. For each one, issues, such as structure, composition, ecology, distribution and relationship with bioclimatic belts and other nearby associations were addressed. Conclusions: The floristic combinations of the associations reflect environmental variations that occur along the altitudinal gradient, including those caused by natural and/or anthropic disturbance. These associations permit a clear classification of the phytocenotic heterogeneity in the forest studied, and confirm its role of environmental service providers and biodiversity.